2021
DOI: 10.1186/s12903-021-01474-7
|View full text |Cite
|
Sign up to set email alerts
|

The optimal orthodontic displacement of clear aligner for mild, moderate and severe periodontal conditions: an in vitro study in a periodontally compromised individual using the finite element model

Abstract: Background Pathologic tooth migration (PTM) is a common complication of mild to severe periodontitis and proper orthodontic treatment is helpful to alleviate periodontal diseases. The goal of this study is to explore an optimal orthodontic displacement of clear aligner using a three-dimensional (3D) finite element model (FEM). Methods The cone beam computed tomography (CBCT) data of a patient received invisible orthodontics without diabetes and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 37 publications
2
34
0
1
Order By: Relevance
“…Moreover, this strain increases even more in subjects with excessively inclined anterior teeth This is a common side effect that is usually addressed during orthodontic therapy of periodontally compromised patients. To avoid the deformation of the alveolar ridge crest in these cases, Ma and Li recommend displacements of less than 0.18 mm for normal alveolar bone, 0.15 mm for 1/3 resorption, and 0.10 mm for 1/3-1/2 resorption [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this strain increases even more in subjects with excessively inclined anterior teeth This is a common side effect that is usually addressed during orthodontic therapy of periodontally compromised patients. To avoid the deformation of the alveolar ridge crest in these cases, Ma and Li recommend displacements of less than 0.18 mm for normal alveolar bone, 0.15 mm for 1/3 resorption, and 0.10 mm for 1/3-1/2 resorption [32].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this treatment involves a form of tooth movement that features a predetermined “mismatch” between the aligner and the tooth. The force produced by the deformation of the appliance is transmitted to the tooth and periodontal tissues, thus causing tooth movement and tissue remodeling [ 2 ]. Over recent years, plastic aligners have been employed for mild to moderate orthodontic tooth movements [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontic treatment is used clinically in patients with anterior tooth displacement. Orthodontic treatment has been reported to enhance the appearance and function of teeth by moving or straightening these pathological teeth [5,6]. However, few studies have shown the e ect of orthodontic treatment on anterior tooth displacement after periodontal disease.…”
Section: Introductionmentioning
confidence: 99%